2003
DOI: 10.1189/jlb.0802401
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of actin polymerization by peroxynitrite modulates neutrophil functional responses

Abstract: Peroxynitrite, a potent oxidant generated in inflammatory tissues, can nitrate tyrosine residues on a variety of proteins. Based on previous studies suggesting that actin might be a potential target for peroxynitrite-mediated nitration in neutrophils, we investigated the effects of peroxynitrite on actin function. We show here that peroxynitrite and the peroxynitrite generator (SIN-1) modified actin in a concentration-dependent manner, resulting in an inhibition of globular-actin polymerization and filamentous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 78 publications
3
41
1
1
Order By: Relevance
“…Nitration seems to stabilize interactions between the pointed end of G-actin and the barbed ends of filaments that may stabilize formation of actin nuclei, accelerate filament elongation, and/or slow subunit dissociation. Actin nitration compromises several neutrophil functions (68). Nitrosylation of the four cysteine moieties closest to the carboxyl terminus clearly effects actin polymerization in several ways (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Nitration seems to stabilize interactions between the pointed end of G-actin and the barbed ends of filaments that may stabilize formation of actin nuclei, accelerate filament elongation, and/or slow subunit dissociation. Actin nitration compromises several neutrophil functions (68). Nitrosylation of the four cysteine moieties closest to the carboxyl terminus clearly effects actin polymerization in several ways (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Its organization in filaments is fundamental for its function. Oxidation and in particular nitration of actin can alter actin polymerization (47). The motor neuron, with its extensive network of cell processes, needs a particularly efficient transport system to transfer cellular components synthesized in the cell body to their correct destination.…”
Section: Fig 3 Nt Immunoreactivity In Ventral Horn Of Transverse Sementioning
confidence: 99%
“…On the other hand, it has been shown that Cys 374 of actin monomer (G-actin) is particularly sensitive to oxidation by hydrogen peroxide [3] and nitric oxide donors [4], which are stress conditions leading to a reduction of the actin polymer (F-actin), that plays a major role in myofibril contraction. Peroxynitrite is an important oxidative stress agent in ischemia/reperfusion insults, such as heart infarct or atrial fibrillation [1,5,6], and inflammation [7], and it has been reported that peroxynitrite can inhibit actin polymerization in neutrophils [8]. Furthermore, in aged muscle, actin is one of the proteins showing higher content of the commonly used fingerprint marker of peroxynitrite-reactive proteins 3-nitrotyrosine [9].…”
Section: Introductionmentioning
confidence: 99%